Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Symbiont transmission and reproductive mode influence responses of three Hawaiian coral larvae to elevated temperature and nutrients - Rebecca M. Kitchen; Madeline Piscetta; Mariana Rocha de Souza; Elizabeth A. Lenz; Daniel W. H. Schar; Ruth D. Gates; Christopher B. Wall (Coral Reefs, 2020)

Reduced Introgression of Sex Chromosome Markers in the Mexican Howler Monkey (Alouatta palliata × A. pigra) Hybrid Zone - Liliana Cortés-Ortiz; Marcella D. Baiz; Javier Hermida-Lagunes; Francisco García-Orduña; Ariadna Rangel-Negrín; Dawn M. Kitchen; Thore J. Bergman; Pedro A. D. Dias; Domingo Canales-Espinosa (International Journal of Primatology, 2019)
Interspecific hybridization allows the introgression or movement of alleles from one genome to another. While some genomic regions freely exchange alleles during hybridization, loci associated with reproductive isolation do not intermix. In many model organisms, the X chromosome displays limited introgression compared to autosomes owing to the presence of multiple loci associated with hybrid sterility or inviability (the “large X-effect”). Similarly, if hybrids are produced, the heterogametic sex is usually inviable or sterile, a pattern known as Haldane’s rule. We analyzed the patterns of introgression of genetic markers located in the mitochondrial (control region) and nuclear (autosomal microsatellites and sex chromosome genes) genomes of two howler monkey species ( Alouatta palliata and A. pigra ) that form a natural hybrid zone in southern Mexico, to evaluate whether the large X-effect and Haldane’s rule affect the outcomes of hybridization between these sister species. To identify the level of admixture of each individual in the hybrid zone ( N = 254) we analyzed individuals sampled outside the hybrid zone (109 A. pigra and 39 A. palliata ) to determine allele frequencies of parental species and estimated a hybrid index based on nuclear markers. We then performed a cline analysis using individuals in the hybrid zone to determine patterns of introgression for each locus. Our analyses show that although the hybrid zone is bimodal (with no known F1 s and few recent generation hybrids) and quite narrow, there has been extensive introgression in both directions, and there is a large array of admixed individuals in the hybrid zone. Mitochondrial and most autosomal markers showed bidirectional introgression, but some had biased introgression toward one species or the other. All markers on the sex chromosomes and a few autosomal markers showed highly restricted introgression. This pattern is consistent with the hypothesis that the sex chromosomes make a disproportionate contribution to reproductive isolation, and our results broaden the taxonomic representation of these patterns across animal taxa.

Temporal but Not Acoustic Plasticity in Hybrid Howler Monkey (Alouatta palliata × A. pigra) Loud Calls - Dawn M. Kitchen; Thore J. Bergman; Pedro A. D. Dias; Lucy Ho; Domingo Canales-Espinosa; Liliana Cortés-Ortiz (International Journal of Primatology, 2019)

Proprioceptive loss and the perception, control and learning of arm movements in humans: evidence from sensory neuronopathy - R. Chris Miall; Nick M. Kitchen; Se-Ho Nam; Hannah Lefumat; Alix G. Renault; Kristin Ørstavik; Jonathan D. Cole; Fabrice R. Sarlegna (Experimental Brain Research, 2018)

Male baboon responses to experimental manipulations of loud “wahoo calls”: testing an honest signal of fighting ability - D. M. Kitchen; D. L. Cheney; A. L. Engh; J. Fischer; L. R. Moscovice; R. M. Seyfarth (Behavioral Ecology and Sociobiology, 2013)

Transport of Poly(Amidoamine) Dendrimers across Caco-2 Cell Monolayers: Influence of Size, Charge and Fluorescent Labeling - Kelly M. Kitchens; Rohit B. Kolhatkar; Peter W. Swaan; Natalie D. Eddington; Hamidreza Ghandehari (Pharmaceutical Research, 2006)

From “Snakebites in the new millennium: A state-of-the-art symposium” - J. Audi; S. A. Seifert; J. F. Gennaro; J. W. Skimming; L. H. S. Van Mierop; C. S. Kitchens; M. D. Cardwell; S. P. Bush; R. T. Clark; E. A. Dugan; R. C. Dart; S. R. Rose; et al. (Journal of Medical Toxicology, 2006)

Coprological Surveys of Alouatta pigra at Two Sites in Belize - Katherine A. Eckert; Nina E. Hahn; Andrew Genz; Dawn M. Kitchen; Michael D. Stuart; Gary A. Averbeck; Bert E. Stromberg; Hal Markowitz (International Journal of Primatology, 2006)

Factors Affecting Reproduction and Mortality Among Baboons in the Okavango Delta, Botswana - D. L. Cheney; R. M. Seyfarth; J. Fischer; J. Beehner; T. Bergman; S. E. Johnson; D. M. Kitchen; R. A Palombit; D. Rendall; J. B. Silk (International Journal of Primatology, 2004)

Differences in native soil ecology associated with invasion of the exotic annual chenopod, Halogeton glomeratus - Jeffrey J. Duda; D. Carl Freeman; John M. Emlen; Jayne Belnap; Stanley G. Kitchen; John C. Zak; Edward Sobek; Mary Tracy; James Montante (Biology and Fertility of Soils, 2003)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Saginaw Gold: A yellow-fleshed potato cultivar with medium-high specific gravity and excellent chip and french fry quality after storage - R. Coffin; R. Chase; N. Thompson; G. Johnston; A. McKeown; M. K. Keenan; D. Craven; R. Kitchen; J. Wilson; R. Y. Yada (American Journal of Potato Research, 1989)